Authoritarian Parenting and Emotional Regulation in Early Childhood: A Theoretical Review across Cultural Contexts - Mohammad Firman Maulana; Rosmidar Rosmidar; Sarah Nasution; Riski Ayu Permata (AL-ISHLAH: Jurnal Pendidikan, 2026)
Emotion regulation in early childhood is a foundational competency influencing social, psychological, and academic outcomes. Parenting style, particularly authoritarian parenting characterized by high control and low emotional responsiveness, has been consistently associated with maladaptive emotional development. This study examines how authoritarian parenting shapes children’s emotion regulation across cultural contexts. This study employed a qualitative library research design, synthesizing 72 peer-reviewed sources published between 2000 and 2024. Using thematic analysis, the review was guided by Erikson’s psychosocial development theory, Gross’s process model of emotion regulation, and Baumrind’s parenting typology to identify key developmental mechanisms. Findings indicate that authoritarian parenting negatively affects children’s emotional development by limiting emotional awareness, expression, and regulatory flexibility. Children exposed to rigid and emotionally dismissive environments tend to rely on maladaptive strategies such as emotional suppression and avoidance, while demonstrating reduced use of cognitive reappraisal. These patterns are associated with increased risks of anxiety, aggression, and emotional dysregulation. Neurodevelopmental evidence further suggests heightened stress reactivity under such parenting conditions. These effects are particularly pronounced in collectivist cultures where strict parenting norms are socially reinforced. Authoritarian parenting disrupts key developmental processes related to autonomy, emotional agency, and adaptive regulation strategies. Although culturally normative in some contexts, its long-term implications remain detrimental to emotional competence. The study underscores the importance of promoting emotionally responsive and autonomy-supportive parenting practices, alongside culturally sensitive interventions to enhance early childhood emotional development.